Effects of organic fertilizers produced from fish pond sediment on growth performances and yield of Malabar and Amaranthus vegetables - Thanh, Dang Trung; Ty, Nguyen Minh; Hien, Nguyen Vinh; Berg, Håkan; Nguyen, Thi Kieu Oanh; Vu, Pham Thanh; Minh, Vo Quang; Da, Chau Thi (Frontiers in Sustainable Food Systems, 2023)
Increasing intensification of aquaculture production requires the development of strategies to reduce it’s environmental impacts such as pollution caused by the discharge of nutrient rich sediments into local water bodies. This research was undertaken to investigate and evaluate the effect of using organic fertilizers produced from pond sludge of freshwater snakehead fish (Channa striata) composted with organic amendments of peanut shells and coir fibre on growth performance indices and yields of Malabar spinach (Basella alba L.) and Amaranth cruentus (Amaranthus L.) vegetables in the dry and wet seasons. A organic fertilizer quality experiment showed that the richest nutrient contents of the produced organic fertilizer was achieved when using 30% sludge mixed with 70% organic amendments (50% peanut shells + 50% coir bibre). This was selected and used for a vegetable cultivation experiment. For the reference treatment only chemical fertilizer was applied, whilst in the other four treatments 25%, 50%, 75% and 100% of the chemical fertilizer was substituted with the organic fertilizer. From 25% to 50% reduction in the chemical fertilizer application resulted in better growth performance indices and final yields than the other treatments, including the reference treatment, for both crops. The highest yields of Malabar spinach and Amaranth cruentus vegetables were found in Treatment 3 (50% chemical fertilizer combined with 50% organic fertilizer) followed by Treatment 2 (25% organic fertilizer combined with 75% inorganic fertilizer) (P˂0.05). The results shows that the reuse of sludge from snakehead fish ponds mixed with agricultural by-products as organic fertilizer for vegetables, not only improve the vegetable productivity, but also reduce the costs for chemical fertilizer and decreases the environmental pollution.